Genome-wide analysis and characterization of Dendrocalamus farinosus SUT gene family reveal DfSUT4 involvement in sucrose transportation in plants - Deng, Bin; Gu, Xiaoyan; Chen, Sen; Zhang, Meng; Hao, Suwei; Wei, Lixian; Cao, Ying; Hu, Shanglian (Frontiers in Plant Science, 2023)
Sucrose is the main transported form of photosynthetic products, sucrose transporter (SUT) participates in the translocation of sucrose from source to sink, which is important for the growth and development of plants. Dendrocalamus farinosus is an important economic crop in southwestern China because of it’s high growth rate, high fiber content and dual usages for food and timber, but the mechanism of sucrose transportation in D. farinosus is unclear. Here, a total of 12 SUT transporter genes were determined in D. farinosus by the whole-genome identification. DfSUT2, DfSUT7 and DfSUT11 were homologs of rice OsSUT2, DfSUT4 was homolog to OsSUT4, and these four DfSUT genes expressed in leaf, internode, node and bamboo shoots of D. farinosus. In addition, DfSUT family genes were involved in photosynthetic products distribution, ABA/MeJA responses and drought resistance, especially DfSUT4. The function of DfSUT4 was then verified in Nicotiana tabacum. DfSUT4 was localized mainly in leaf mesophyll and stem phloem of pDfSUT4::GUS transgenic plant. The overexpression of DfSUT4 gene in transgenic plant showed increases of photosynthetic rate, above-ground biomass, thousand grain weight and cellulose content. Altogether, our findings indicate that DfSUT4 can be a candidate gene that be involved in the phloem sucrose transportation from source leaves to sink organs, phytohormone responses, abiotic stress and fiber formation in plants, which is very important in the genetic improvement of D. farinosus and other crops.